Manajemen Stres Kerja Dan Peningkatan Kesejahteraan Karyawan Dalam Psikologi Organisasi - Merika Setiawati; Masaati Laoli; Ativa Mardatila; Amar Saipul Ali Azwar (GLOBAL SCIENTS PUBLISHER, 2025)
Work stress has become a significant challenge in modern organizations, impacting employee well-being and productivity. This literature review examines the determinants of work stress, its effects on psychological well-being, and effective management strategies within organizational psychology. Key findings indicate that factors such as excessive workload, role conflicts, and lack of social support contribute to stress, leading to reduced performance, burnout, and mental health issues. Interventions like Cognitive Behavioral Therapy (CBT), mindfulness practices, and organizational support programs can mitigate these effects, enhancing employee well-being and organizational outcomes. Recommendations emphasize integrated individual and organizational approaches for sustainable stress management